Konsep Pembebasan Perempuan Qasim Amin Menuju Pemberdayaan Modern - Aini, Siti Nur (Maliki Interdisciplinary Journal, 2024)
Different approaches to feminism in the West such as liberal, Marxist, radical and socialist feminism are used to study feminism. On the other hand, in the Arab-Islamic world, feminism is still a controversial subject, with many people being for, against, or even anti-feminism. Although women's issues are still a historical problem in the Arab world, especially in Egypt, the Amin Reforms had a significant influence on the development of feminism throughout the Arab-Islamic world. Egypt even became the center of discussion (al-markaziyyah al-fikriyyah) about the problem of women's oppression in history. Signs of a liberation movement, or feminism, emerged when practices of subordination and marginalization emerged. Qasim Amin and Jamal al-Banna, two Muslim feminists, attempted to outline the debate about women's liberation. In their discourse on women's liberation, Amin and Jamal used their own feminist perspective. They stated that it was not religion that caused women to be marginalized and subordinated, but culture and religious misunderstandings. This study investigates the idea of ​​"Tahrir al-Mar'ah", which is regarded as the central Qasim Amin's reforms. The feel of achievement and invest of girl is the basis of this idea. This idea emerged as a reflection and proof of intellectual fear for the situation of Egyptian women who had crossed the local tolerance threshold. Data sources for this research are books, journals and other sources, which are used using library research methods. Therefore, the data was analyzed using content analysis. Because Islamic values ​​contain justice and responsibility to Allah, Qasim Amin emphasized that women must have the same educational rights as boy and girl.